2013
DOI: 10.1890/12-1399.1
|View full text |Cite
|
Sign up to set email alerts
|

Root depth distribution and the diversity–productivity relationship in a long‐term grassland experiment

Abstract: Abstract. The relationship between plant diversity and productivity in grasslands could depend, partly, on how diversity affects vertical distributions of root biomass in soil; yet, no prior study has evaluated the links among diversity, root depth distributions, and productivity in a long-term experiment. We used data from a 12-year experiment to ask how plant species richness and composition influenced both observed and expected root depth distributions of plant communities. Expected root depth distributions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
255
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(277 citation statements)
references
References 35 publications
19
255
2
1
Order By: Relevance
“…Although we cannot rule out that the proposed mechanisms are particularly pronounced at the field site of The Jena Experiment, the underlying relationships between plant diversity and soil carbon storage 17,24 , soil microbial biomass and activity 37,45,46 , and root biomass 24,47 have been reported in several independent experimental settings providing some evidence that the proposed links are of general significance. This leads us to reconsider the role of soil microorganisms as sources rather than sinks for slow-cycling organic matter.…”
mentioning
confidence: 87%
“…Although we cannot rule out that the proposed mechanisms are particularly pronounced at the field site of The Jena Experiment, the underlying relationships between plant diversity and soil carbon storage 17,24 , soil microbial biomass and activity 37,45,46 , and root biomass 24,47 have been reported in several independent experimental settings providing some evidence that the proposed links are of general significance. This leads us to reconsider the role of soil microorganisms as sources rather than sinks for slow-cycling organic matter.…”
mentioning
confidence: 87%
“…The total productivity of diverse plant communities may also partly depend on below-ground interactions that cause overall roots to be distributed deeply in soil profiles. Mueller et al (2013) evaluated the links among diversity, overall root depth distribution and total productivity using data from a 12-year experiment, and observed that the overall proportion of deep-root biomass increased with species richness and was positively correlated with above-ground productivity in artificial grasslands. Mommer et al (2015) recently showed that diversity enhanced overall root length and decreased total root loss and root mortality of the whole community, resulting in root overproduction in an experimental grassland community.…”
Section: Relationships Between Interspecific Root Interactions and Abmentioning
confidence: 99%
“…Consequently, increased diversity in BioCON results in greater competition for resources and greater potential for facilitation under a higher-density canopy (Adair et al 2011, Mueller et al 2013, Wright et al 2013. For the purposes of this experiment, we utilized this biodiversity gradient to simultaneously manipulate both competition (via reduction in resource availability) and facilitation (via amelioration of environmental conditions).…”
Section: Study Site and Experimental Designmentioning
confidence: 99%